Report on Evaluation of Consolidation of Holdings Programme April 1969 - Planning Commission (Planning Commission, 1969)
At the instance of the Planning Commission, the Programme Evaluation Organisation undertook an evaluation study of the Consolidation of Holdings programme. the study was undertaken in eight States where more than 4.05 lakh hectares of land were consolidated. The sample consists of 18 districts, 36 tehsils/talukas, 106 villages and about 1,100 cultivators.
Programme Evaluation Organisation Government of India Planning Commission